Digital Trust in Purchasing Processes – Perspective of Relationships With Stakeholders During the COVID-19 Pandemic - Wioletta WEREDA; Jacek WOŹNIAK (Communications of International Proceedings, 2021)
Nowadays, customers in many countries in the world – in the conditions of the COVID-19 pandemic – go into online shopping model, i.e. using ICTs. This increases the role and importance of digital trust (which enables decisions and interactions between two or more actors based on their digital reputation and ability to protect data). In order to properly shape the relationship with stakeholders in purchasing processes, customers need to be aware of the level of digital trust. Thus, the aim of the study is to assess the level of the complexity of digital trust of customers in purchasing processes to different stakeholder groups, as well as identify the characteristics of customers who have a high level of the complexity of digital trust during the COVID-19 pandemic. The empirical study was conducted (between March 2020 and April 2020) in the CATI form on a sample of 320 Polish customers who regularly make online purchases (at least 5 purchases in electronic form in the last 6 months). The data analyses were supported by the IBM SPSS Statistics version 26. The research methods are as follows: the analysis of basic descriptive statistics, cluster analysis (k-means method), Friedman's rank test, as well as factor analysis (i.e. Principal Components Analysis method – PCA). In particular, the study showed that: (1) the complexity of digital trust in customers' opinion (in purchasing processes) is not at a high level under the COVID-19 pandemic, (2) relationships with employees of the organization (i.e. with the internal stakeholders) are of a high importance in shaping the complexity of digital risk in purchasing processes during the COVID-19 pandemic, (3) generation of Customers 4.0 is not characterized by a high level of the complexity of digital trust (in purchasing processes) under the COVID-19 pandemic, (4) customers who have a high use of social media in purchasing processes are not characterized by a high level of the complexity of digital trust under the COVID-19 pandemic, as well as (5) customers who have a high use of ICTs (IT devices) in purchasing processes are characterized by a high level of the complexity of digital trust under the COVID-19 pandemic.
Keywords: Digital Trust; Digital Risk; Security; Purchasing Processes; Stakeholders.